Kualitas Pupuk Organik Cair dengan Penambahan Bioaktivator Limbah Buah Mengkudu pada Waktu Fermentasi yang Berbeda - Semaun, Rahmawati; Munir; Rauf, Juliawati (Jurnal Galung Tropika, 2024)
This research aims to obtain quality liquid organic fertilizer (LOF) by using cattle urine and noni-fruit waste as raw materials for LOF at optimal fermentation times. This research used a Completely Randomized Design (CRD) with 4 treatment levels and 3 replications with sampling times based on different time variations, namely 7 days, 14 days, 21 days, and 28 days. This research shows that treatments with different fermentation times did not significantly affect the quality of liquid organic fertilizer, especially the Nitrogen (N) and Phosphorus (P) content. However, there was a tendency to increase the N and P content. The highest average N content was in the Fermentation treatment. For 3 weeks, namely 1.34%, and the highest average P content in the Fermentation treatment for 4 weeks, namely 0.44%. Meanwhile, the average potassium (K) content significantly differed in the 4-week fermentation treatment, namely 0.43%. Overall, the best N, P, and K content for all observed parameters was POC fermentation for 4 weeks (fermentation day 28).